Successful New Economic Model (NEM) implementation through improvement fishery sector / Norfatimah Othman - Othman, Norfatimah (2011)
The main idea behind new economic model (NEM) is to achieve Vision 2020. Vision 2020 is to develop high income nation in year 2020. The NEM will create a framework to the Malaysia in the future that will be renowned for vibrant transformation arising from the resourcefulness of its people exemplified by its harmonious diversity and rich cultural traditions. In addition, new economic model also will provide the framework and environment to engender the entrepreneurial spirit to make the most of growth opportunities from available financing. New economic model will provide modus operandi to Lembaga Kemajuan Ikan Malaysia and Jabatan Perikanan Malaysia to be more develop sector in the future. Nowadays, fishery sector plays important roles to the growth of Malaysia’s economic. Built on the perception studies framework, the purpose of this study is to investigate the successful new economic model implementation through improvement of fishery sector. The improvement of fishery sector is measured by subsidies,loans or financial supports,fishing equipment and lack of ice or freezer room. The target population of this study is all fishermen in Terengganu and members of Persatuan Nelayan Kawasan Kuala Terengganu Selatan(PNKKTS). Based on the regression results,subsidies,loans or financial supports and fishing equipment have positive significant effects on improvement of fishery sector in order to implement New Economic Model to be successful. However, lack of ice or freezeer room have no significant relationship on improvement of fishery sector. Moreover, based on the hypothesis testing it also show that, only subsidies,loans and fishing equipment have significant relationship on improvement fishery sector towards successful New Economic Model implementation. Referring to this relationship, it can be presumed that improvement fishery sector in terms of subsidies,loans and fishing equipment give positive effect to the successful New Economic Model implementation